TINJAUAN ‘URF TERHADAP TRADISI MANGGADAIKAN ANAK KARENA TA IMPOK PALAPA NDAYANG OLEH MASYARAKAT MUARA KANDIS PUNGGASAN - Insani, Silvi Sri; Zulfan, Zulfan; Ikhwan, Ikhwan (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
This research was conducted to examine the tradition of pawning children because of the ta impok palapa ndayang by the Muara Kandis Punggasan community. This tradition is a hereditary custom where children who have impok palapa ndayang will be pawned to the bako. This habit is believed by the community to protect children from bad things and maintain family harmony. This research aims to describe the process of implementing this tradition in Muara Kandis Punggasan and review the perspective of Islamic law ('urf) towards this custom. The research method used is qualitative with a descriptive approach. Data was collected through observation, interviews and documentation studies with informants consisting of communities directly involved in this traditional practice as well as local traditional leaders. The results of the research show that the process of implementing the tradition of pawning children involves several stages, including selecting the child who will be impok palapa ndayang, accepting the pawn by the bako, handing over the child, and redeeming the pawn. This tradition is carried out with the belief that if it is not implemented, it can have negative consequences for the family.